Aesthetic security to enhance farmers’ income - Prasad, K V; Kadam, Ganesh; Saha, Tarak Nath (Indian Horticulture, 2019)
India exported floricultural produce worth `450 crores, comprising fresh cut flowers to Europe, Japan, Australia, Middle East and USA; loose flowers for expatriate Indians in the Gulf and Europe; cut foliage to Europe; dry flowers to USA, Europe, Japan, Russia and Australia and potted plants to Middle East besides seeds and planting material. The major market for domestic flowers is in Delhi, Mumbai, Kolkata, Chennai, Pune, Bengaluru, Hyderabad etc. With limited infrastructure the amount of trade that takes place in the major markets varies from season-to-season. The market value of the traditional flowers is not well documented leaving mostly to speculations. Estimates suggest that the domestic trade of flowers is more than `1,000 crores.